Factoring: Alternative model of financing - Sasa Ivanovic; Suzana Baresa; Bogdan Sinisa (UTMS Journal of Economics, 2011)
This paper aims to present factoring as an alternative funding model. This paper also tries to scientifically explore and emphasize its economic role thorough advantages and disadvantages of such financing model, and show condition in world and Croatia. Good corporate governance and professional financial management can contribute to the establishment of such business strategy (in terms of: strategy in relation to potential risks, the systems for managing risks and monitoring, investment strategies, interventions, etc.) that will make the company resistant to unexpected and unpredictable changes in both their environment and the global marketplace and timely actions to contribute to faster recover from the effects of the crisis and business damages reduced to a minimum recovery.
Keywords: B26; D53; D92; G21; 330; factoring; receivables; liquidity; solvency; financing.